A STUDY TO ANALYZE SPELLING MISTAKES COMMITTED BY ENGLISH LEARNERS AT HIGHER SECONDARY SCHOOL LEVEL - Aneesa Majeed; Samina Yasmin; Shahbaz Khalid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The aim of the present study was to analyze spelling mistakes committed by English learners of higher secondary schools in Lahore district. It was descriptive research based on cross sectional survey design in nature. The major purpose of this research was to find out types of committed spelling mistakes and knowing about which types of spelling mistakes are committed by English learners the most at higher secondary school level. In this regards, data was gathered of 280 students who were studying in 12th class by applying systematic random sampling technique via collecting their last two administered English Language tests from 8 randomly selected higher secondary schools of Lahore district. Text analysis technique was used for listing and classifying spelling mistakes committed by the second year English learners. To find out demographic variables wise differences in the committing of mistakes, inferential and descriptive statistics was applied to analysis the data with help of SPSS (V.21) software. The result shows that majority of the English learners committed omission, substitution, and transposition spelling mistakes, and the most committing spelling mistakes at higher secondary school level are omission spelling mistakes. Statistically significant locality wise difference was found among English learners in committing spelling mistakes. It was also found that among the English learners, the majority boys of government higher secondary schools of rural areas and majority girls of the government higher secondary schools of urban areas committed omission errors while majority girls of the government higher secondary schools of rural areas and majority boys of the government higher secondary schools of urban areas, committed transposition/ disordering types of spelling errors. It is recommended that at secondary school level, while teaching English in the classroom, English teaching should share the rules of writing English with students to avoid spelling mistakes. Moreover, education department should also arrange continuous professional development training for language teachers to improve their language skills.